(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this study is to assess the influence of brand image on consumer loyalty, focusing on Tata Motors and Maruti Suzuki India Limited, key players in the Indian automotive industry. Employing a quantitative research approach, Structural Equation Modeling (SEM) was utilized to explore the intricate relationship between brand image and consumer loyalty. Methods: A quantitative research design was employed, utilizing structured questionnaires administered to 400 consumers visiting Tata Motors and Maruti Suzuki India Limited showrooms. Data collection encompassed perceptions of brand image and loyalty indicators, with demographic information collected for sample representativeness. Normality checks preceded SEM analysis, ensuring data validity. Results: Analysis revealed a robust positive correlation between brand image and consumer loyalty. Favorable brand perceptions significantly influenced consumer loyalty, evidenced by increased repurchase intentions. These findings align with existing literature, emphasizing the pivotal role of brand image in shaping consumer behavior and fostering loyalty. Conclusion: This study contributes empirical evidence of brand image’s substantial impact on consumer loyalty within the automotive sector. Understanding this relationship enables companies to strategically manage brand image, enhancing consumer trust and fostering lasting brand allegiance. Implications: Practical implications include investment in brand image enhancement through product quality improvement, customer experience optimization, and brand differentiation. Building brand communities and continuous monitoring are also crucial for sustained brand relevance and competitiveness.